Impact of Public Spending Efficiency on Surabaya's Economic Development - Navoleon, Alfaridho (Journal of Sustainable Community Development (JSCD), 2024)
This analysis aims to evaluate the impact of public sector spending efficiency on the performance of economic development in Surabaya City. The main focus of this analysis is to understand the relationship between public sector spending efficiency and various indicators of economic development, including regional gross domestic product (GDP) and unemployment rates. The method used in this research is quantitative descriptive, with data taken from secondary sources, such as the Central Statistical Agency of East Java. The data is analyzed to identify patterns and trends that show how efficiency in public spending can affect economic growth and the decline in the unemployment rate in the city. The findings of this analysis are expected to provide a deep insight into the correlation between efficient public sector budget management and economic progress in Surabaya. This insight is crucial for policymakers and other stakeholders in formulating effective strategies to improve the city's economic performance. In addition, this research can also serve as a reference for further studies in urban economics and public finance management. Thus, this analysis not only provides an overview of the current economic conditions, but also provides directions for better economic policy development in the future.